Odpowiedzi

Najlepsza Odpowiedź!
2010-02-17T14:52:43+01:00
1/5x-3=x+1/5
1/5x-x=1/5+3
-4/5x=3 1/5
-4/5x=16/5 : 4/5
x= 4/5

5/6(x-1)=4
5/6x-5/6=4
5/6x=4+5/6
5/6x=29/6 : 5/6
x=5,8/6

-1/2(-x-6)=-x
1/2x+3=-x
1/2x+x=-3
3/2x=3 : 3/2
x=2
1 5 1
2010-02-17T14:56:20+01:00
X/5-3=x+1/5
x/5-x=1/5+3
x/5-5x/5=1/5+15/5 sprowadzone do wspolnego mianownika
-4x/5=16/5 to mnożymy po przekątnej
-20x=80/:(-20)
x=-4
5/6(x-1)=4
5x/6-5/6=4
5x/6=4+5/6
5x/6=4 ⁵/₆
5x/6=³¹/₆ to mnoze po przekatnej
30x=186/:30
x=6,2
-1/2(-x-6)=-x
x/2+3=-x
x/2+x=-3
x/2+2x/2=-3
3x/2=-3to mnożymy po przekątnej -3 to tak jak 3/1
3x=-6/;3
x=-2
1 5 1